Sarcomatoid mesothelioma diagnosed in a patient with mesothelioma in situ: a case report on morphologic differences after 9-month interval with details analysis of cytology in early-stage mesothelioma - Miho Yoshida; Naoe Jimbo; Ryuko Tsukamoto; Tomoo Itoh; Kunimitsu Kawahara; Suguru Mitsui; Yugo Tanaka; Yoshimasa Maniwa (BMC, 2023)
Abstract Background Overlapping morphological features of mesothelial cells have been rendered it difficult to distinguish between reactive and malignant conditions. The development of methods based on detecting genomic abnormalities using immunohistochemistry and fluorescence in situ hybridization have contributed markedly to solving this problem. It is important to identify bland mesothelioma cells on cytological screening, perform efficient genomic-based testing, and diagnose mesothelioma, because the first clinical manifestation of pleural mesothelioma is pleural effusion, which is the first sample available for pathological diagnosis. However, certain diagnostic aspects remain challenging even for experts. Case presentation This report describes a case of a 72-year-old man with a history of asbestos exposure who presented with pleural effusion as the first symptom and was eventually diagnosed as mesothelioma. Mesothelioma was suspected owing to prominent cell-in-cell engulfment in mesothelial cells on the first cytological sample, and the diagnosis of mesothelioma in situ was confirmed by histology. Unexpectedly, sarcomatoid morphology of mesothelioma was found in the second pathology samples 9 months after the first pathological examination. Both the mesothelioma in situ and invasive lesion showed immunohistochemical loss of methylthioadenosine phosphorylase (MTAP) and homozygous deletion of cyclin dependent kinase inhibitor 2A (CDKN2A) on fluorescence in situ hybridization. The patient received medication therapy but died of disease progression 12 months after the diagnosis of the sarcomatoid morphology of mesothelioma. Conclusion Our case suggests that cell-in-cell engulfment can be conspicuous in early-stage mesothelioma with inconspicuous nuclear atypia and few multinucleated cells. In addition, the presence of MTAP loss and CDKN2A homozygous deletion are suspected to be involved in early formation to invasive lesions and/or sarcomatoid morphology. We believe that it is important to consider genetic abnormalities when deciding on individual patient management. Furthermore, cases of mesothelioma, even those of an in situ lesion, with MTAP loss and/or CDKN2A deletion should be carefully followed up or subjected to early treatment.